Strategies of Community Leaders in Creating Social Harmony in Teluk Batu Selatan Hall, Randai Village, Marau District, Ketapang Regency - Syarmiati; Rupita; Zulkarnain; Fitriani, Nurul Amira; Indriani, Maulidya (GoAcademica Research & Publishing, 2025)
This article discusses the strategy of community leaders in creating social harmony in Teluk Batu Selatan Hamlet, Randai Village, Marau District, Ketapang Regency. This research uses qualitative methods in a descriptive form. This research will collect data from the research subjects by purposive means, meaning that the research subjects are taken from people who are directly involved and understand the problems regarding community social interaction in Teluk Batu Selatan Hamlet, Randai Village, Marau District, Ketapang Regency. The data were analyzed using data checking techniques, which were carried out in this study through data source triangulation. This involved exploring the truth of certain information through interviews and observations. The results of the study are expected to provide valuable insights for the community in Teluk Batu Selatan Hamlet, Randai Village, Marau District, Ketapang Regency.